Hydrogenase on an electrode: a remarkable heterogeneous catalyst - Lamle, SE; Vincent, K; Halliwell, L; Albracht, S; Armstrong, F (2003)
Hydrogenases - enzymes interconverting hydrogen and water - display intriguing chemistry and offer important possibilities for future energy technologies. The so-called [NiFe]-hydrogenases contain a binuclear NiFe catalytic center coordinated by thiolates, CO and CN-. Hydrogenases pose significant experimental challenges due to O2-sensitivity, high activity, and the presence of many different active and inactive states. However, the enzyme can be studied with considerable precision using a minuscule quantity adsorbed on an electrode. In this form it is a heterogeneous catalyst rather than the solution system studied by enzymologists: in particular, exploitation of the 'potential dimension' enables complex reactions to be analysed and deconvoluted.